2014
DOI: 10.1002/eco.1528
|View full text |Cite
|
Sign up to set email alerts
|

More complexity does not always mean more accuracy: the case of IBMWP and METI in NW Spain

Abstract: Since the Water Framework Directive (WFD) implementation, new biological indices based on macroinvertebrates have been developed, mainly focusing on multimetric approaches. This work checks the relationship among several biotic indices [Iberian Biological Monitoring Working Party (IBMWP), Indice Biotico Esteso, Indice Biologique Global Normalisé] and one multimetric index (METI) proposed for NW Spain rivers, and their behaviour using different physicochemical parameters throughout the different typologies defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 72 publications
2
17
0
2
Order By: Relevance
“…These results are in agreement with Use of photoperiod manipulation to alter the incidence of sexual maturation and the time of spawning has been reported for a number of species (Duston et al, 2003;Imsland et al, 2003). Mendoza et al (2014) found significantly larger eggs under normal day length (12 L: 12 D). However, (Ridha and Cruz, 2000) found that fish reared under long day length (18 L: 6 D) exhibited higher total fecundity and relative fecundity, with a reduction in inter-spawnintervals.…”
Section: The Results Insupporting
confidence: 91%
“…These results are in agreement with Use of photoperiod manipulation to alter the incidence of sexual maturation and the time of spawning has been reported for a number of species (Duston et al, 2003;Imsland et al, 2003). Mendoza et al (2014) found significantly larger eggs under normal day length (12 L: 12 D). However, (Ridha and Cruz, 2000) found that fish reared under long day length (18 L: 6 D) exhibited higher total fecundity and relative fecundity, with a reduction in inter-spawnintervals.…”
Section: The Results Insupporting
confidence: 91%
“…The IBMWP index is a single metric index (Munné and Prat, 2009) and the sample value is obtained by summing these family scores. This index is considered a simple one (Couto-Mendoza et al, 2015) with a multihabitat semi-quantitative kick procedure in the field (Jáimez-Cuéllar et al, 2002). IASPT represents a sensitive taxa index that is easily calculated for each sample as the IBMWP value divided by the number of scoring families detected.…”
Section: Macroinvertebrate Indices: Ibmwp Iaspt and Star_icmimentioning
confidence: 99%
“…Similarly, the potential advantages of multimetric indices over single metric indices should also be considered; this topic has already been subject of debate in some instances (e.g. Couto-Mendoza et al, 2015). To avoid criticisms associated with scoring systems limited to faunal tolerances in relation to a single parameter (a common criticism of the BMWP approach which focuses on organic contamination), a multimetric approach would facilitate the assessment of multiple stressors (e.g., potentially including the presence and impacts of new invaders).…”
Section: Discussionmentioning
confidence: 99%